Evaluation of literary texts included in the Arabic language book for the third intermediate grade in the light of creative thinking skills (Journal of the College of Basic Education, 2023)
To achieve the goal of the research, the researcher adopted the descriptive approach as a method for his study, because it is the appropriate approach to achieve the goal of the research. The research community consisted of Arabic language teachers and female teachers for the third intermediate grade in the General Directorates of Education in the governorate of Baghdad six, for the academic year 2021-2022, and their number is (1126) teachers. and school, and the researcher randomly chose the research sample to be representative of the research community, as it amounted to (166(A teacher and his teacher in the six general directorates of education, Baghdad. As for the research tool, it was a questionnaire for creative thinking skills. The validity of the tool (the questionnaire) was confirmed by presenting it to the arbitrators. The questionnaire included (8) indicators, distributed over (3) skills, and Data collection and statistical analysis of the results using the weighted mean and percentage weight, the researcher reached results, including: 1- The indicator (the content includes various alternatives for solving scientific problems in more than one way) ranked first with a weighted mean (13.3) and a percentage weight (4,62(2- Indicator (8) (the content directs the student to express the solution in his own language) ranked last with a weighted mean of (56.2) and a weight percentile of (2.51)